일부 전문대학 치위생과 교육 서비스 품질이 학생만족도에 미치는 영향 - 신선행; Seon-haeng Shin (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: The purpose of the study is to investigate the influence of education service quality on major satisfaction in the dental hygiene students. Methods: A self-reported questionnaire was completed by 271 dental hygiene students in Seoul from April 1 to 20, 2016. The questionnaire consisted of general characteristics of the subjects(6 items), education service quality (27 items), and major satisfaction of students(23 items). The instrument for education service quality was adapted from Parasuraman and modified by Park & Lee. Likert 5 point scale adaptation included physical environment, reliability, responsiveness, certainty, empathy, class ㆍprofessors, administrativeㆍfacilities, and school activities.accessibility. Cronbach``s alpha test in the study was 0.956 in education service quality and 0.951 in major satisfaction. Results: The education service quality was 3.1 points. The lower grade students tended to have the higher education service quality (p<0.001). The satisfaction to classㆍprofessors was 3.2 points. The education service quality had a significant positive relation to major satisfaction. The satisfaction was positively influenced by physical environment, responsiveness, certainty, and empathy. Conclusions: A positive motivation to education service quality leads to major satisfaction. A variety of strategies are very important to enhance the education specialization.